A Research Paper on Negation Handling: Sentiment Analysis Using Super Ensemble Method in Deep Learning - Garg, Sarita Bansal; Subrahmanyam, V. V. (Indian Journal of Computer Science, 2023)
Sentiment analysis, a vital technique for comprehending the ideas and attitudes represented in natural language text includes negation handling as a key component. The technique of automatically identifying and categorising the polarity of the sentiment expressed in a text, which might be positive, negative, or neutral, is known as sentiment analysis. Negation handling is tricky too because words like "not", "no", and "never" can flip the polarity of a mood, making it challenging to recognise the sentiment being represented. Therefore, in this research paper, a model is proposed using the super ensemble technique which can correctly comprehend the sentiments expressed in the reviews and give approximately 96% accuracy.